Electrolyte for lithium secondary battery and lithium secondary battery including the same
Incorporating magnesium chloride into the electrolyte of lithium-sulfur batteries forms a protective layer that addresses the migration of lithium polysulfide, reducing dendrite formation and enhancing battery lifespan and efficiency.
Patent Information
- Application Number
- JP2022579100
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-07
- Filing Date
- 2021-12-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-12-16
AI Technical Summary
Lithium-sulfur batteries face significant challenges due to the migration of lithium polysulfide to the negative electrode, leading to irreversible capacity loss, dendrite formation, and reduced lifespan, primarily due to side reactions and consumption of salts and additives in the electrolyte.
Incorporating magnesium chloride (MgCl2) into the electrolyte, along with specific solvents and lithium salts, forms a stable electrode protective layer that suppresses dendrite growth and enhances lithium charging and discharging efficiency.
The electrolyte solution improves the lifespan of lithium secondary batteries by forming a protective layer that prevents the consumption of salts and additives, thereby increasing battery capacity and efficiency.
Smart Images

Figure 0007603723000004 
Figure 0007603723000005 
Figure 0007603723000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0001802 filed on January 7, 2021, and all contents disclosed in the documents of said Korean patent application are incorporated herein by reference.
[0002] The present invention relates to an electrolyte for a lithium secondary battery and a lithium secondary battery including the same, and more particularly, to an electrolyte for a lithium secondary battery and a lithium secondary battery including the same, which can improve the life of the lithium secondary battery by including a certain amount of magnesium chloride (MgCl2) in the electrolyte to form a stable electrode protective layer that prevents consumption of salts and additives in the electrolyte. [Background technology]
[0003] As interest in energy storage technology continues to grow, the fields of application are expanding to include energy in mobile phones, tablets, laptops, and video cameras, as well as electric vehicles (EVs) and hybrid electric vehicles (HEVs), and research and development of electrochemical devices is gradually increasing. Electrochemical devices are the field that has attracted the most attention in this regard, and among them, the development of secondary batteries such as rechargeable lithium-sulfur batteries has become a focus of attention, and recently, the development of such batteries has led to research and development of new electrode and battery designs in order to improve capacity density and specific energy.
[0004] Among these electrochemical devices, lithium metal secondary batteries such as lithium-sulfur batteries (Li-S batteries) are attracting attention as next-generation high-capacity secondary batteries that can replace existing secondary batteries such as lithium-ion batteries, as they not only use lightweight lithium metal as the negative electrode active material, but also have a high energy density (theoretical capacity: 3,862mAh / g). In such lithium-sulfur batteries, a reduction reaction of sulfur and an oxidation reaction of lithium metal occur during discharge, at which time sulfur changes from a ring-shaped S8 to a linear-shaped lithium polysulfide (LiPS). The lithium-sulfur battery is characterized by a stepwise discharge voltage until the polysulfide is completely reduced to Li2S.
[0005] However, the biggest obstacle to the commercialization of lithium-sulfur batteries is their lifespan, as the charge / discharge efficiency decreases during the charging and discharging process, shortening the battery's lifespan. There are various reasons why the lifespan of lithium-sulfur batteries deteriorates, including side reactions of the electrolyte (accumulation of by-products due to the decomposition of the electrolyte), instability of lithium metal (growth of dendrites on the lithium anode, causing short circuits), and accumulation of by-products on the cathode (elution of lithium polysulfide from the cathode).
[0006] That is, in a battery using a sulfur-based compound as a positive electrode active material and an alkali metal such as lithium as a negative electrode active material, the elution and shuttle phenomenon of lithium polysulfide occurs during charging and discharging, and the lithium polysulfide is transferred to the negative electrode, reducing the capacity of the lithium-sulfur battery, which causes a major problem of reduced lifespan and reduced reactivity of the lithium-sulfur battery. That is, since polysulfide eluted from the positive electrode has high solubility in organic electrolyte, it may undesirably move to the negative electrode by the electrolyte (PS shuttling), resulting in a reduction in capacity due to irreversible loss of the positive electrode active material and a reduction in battery life due to the deposition of sulfur particles on the surface of the lithium metal due to side reactions.
[0007] In particular, lithium, which is an anode active material, easily forms large-area dendrites and reacts with salts and additives in the electrolyte to form a solid electrolyte interphase (SEI), which continuously consumes salts and additives in the electrolyte, thereby accelerating the degradation of the battery.
[0008] Meanwhile, the behavior of such lithium-sulfur batteries can vary greatly depending on the electrolyte, and an electrolyte in which sulfur from the positive electrode dissolves into the electrolyte in the form of lithium polysulfide (LiPS) is called catholyte, and an electrolyte in which sulfur is hardly dissolved in the form of lithium polysulfide is called sparingly soluble or solvating electrolyte (SSE). In other words, various researches (such as adding LiPS adsorbent to the positive electrode composite or modifying the existing separator made of PE) have been conducted in the industry on lithium-sulfur batteries in which sulfur, the positive electrode active material, does not dissolve into the electrolyte, and in particular, researches have been conducted on electrolytes in which sulfur can undergo a solid-to-solid reaction with Li2S, the final discharge product, but so far no significant results have been obtained. Therefore, a more fundamental method is required to suppress the phenomenon in which lithium polysulfide migrates to the negative electrode, shortening the life of the lithium-sulfur battery, and the reactivity is reduced due to a large amount of lithium polysulfide.
[0009] Therefore, the industry has been trying to prevent the side reaction problem of the electrolyte, but it has been difficult to fundamentally solve the problem. Therefore, there is a need to develop an electrolyte for lithium secondary batteries that can improve the performance of lithium secondary batteries by forming a stable electrode protective layer that prevents the consumption of salts and additives in the electrolyte. Summary of the Invention [Problem to be solved by the invention]
[0010] Therefore, an object of the present invention is to provide an electrolyte for a lithium secondary battery, which can improve the life of the lithium secondary battery by including a certain amount of magnesium chloride (MgCl2) in the electrolyte to form a stable electrode protective layer that prevents consumption of salts and additives in the electrolyte, and a lithium secondary battery including the same. [Means for solving the problem]
[0011] In order to achieve the above object, the present invention provides an electrolyte for a lithium secondary battery, comprising: a first solvent containing a heterocyclic compound which may or may not contain one or more double bonds and which contains one or more oxygen atoms and sulfur atoms; a second solvent containing one or more of an ether compound, an ester compound, an amide compound, and a carbonate compound; a lithium salt; magnesium chloride; and lithium nitrate.
[0012] The present invention also provides a lithium secondary battery comprising: a positive electrode; a lithium negative electrode; a separator interposed between the positive electrode and the negative electrode; and the electrolyte for the lithium secondary battery. Effect of the Invention
[0013] The electrolyte for lithium secondary batteries and the lithium secondary batteries including the electrolyte according to the present invention have an advantage that the life of the lithium secondary batteries can be improved by adding a certain amount of magnesium chloride (MgCl2) to the electrolyte to form a stable electrode protective layer that prevents the consumption of salts and additives in the electrolyte. [Brief description of the drawings]
[0014] [Figure 1] 1 is a graph showing cycle life performance of lithium-lithium symmetric cells manufactured according to an embodiment of the present invention and a comparative example. [Diagram 2] 1 is a graph showing cycle life performance of lithium-sulfur batteries manufactured according to an embodiment and a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] The electrolyte for a lithium secondary battery according to the present invention comprises: A) a first solvent containing a heterocyclic compound which may or may not contain one or more double bonds and which contains one or more oxygen atoms and sulfur atoms; B) a second solvent containing one or more of an ether compound, an ester compound, an amide compound, and a carbonate compound; C) a lithium salt; D) magnesium chloride; and E) lithium nitrate.
[0017] The electrolyte applicable to lithium secondary batteries such as lithium-sulfur batteries leads to differences in performance such as battery life or efficiency depending on the types of solvent, lithium salt, and additives contained in the electrolyte. Therefore, the applicant has conducted extensive research to improve the performance of lithium secondary batteries and found that the capacity and life of lithium secondary batteries can be improved by combining the solvent, lithium salt, and additive (magnesium chloride, MgCl2) contained in the electrolyte of the lithium secondary battery in an optimal ratio. In particular, magnesium chloride (MgCl2) reacts with the lithium negative electrode to form a LiCl protective layer on the surface of the negative electrode and forms a lithophilic Li-Mg alloy to improve lithium charge and discharge efficiency and inhibit the growth of dendrites (i.e., the battery capacity is increased by improving the lithium usage efficiency).
[0018] Hereinafter, A) the first solvent, B) the second solvent, C) the lithium salt, D) magnesium chloride, and E) lithium nitrate contained in the electrolyte solution for a lithium secondary battery of the present invention will be specifically described.
[0019] A) First Solvent The first solvent includes a heterocyclic compound containing one or more double bonds and one or more oxygen atoms and sulfur atoms. The first solvent has a characteristic of being difficult to dissolve salt due to the delocalization of lone pair electrons of the heteroatom (oxygen atom or sulfur atom). Therefore, the first solvent can form a polymer protective film (solid electrolyte interphase, SEI layer) on the surface of the lithium-based metal (negative electrode) through a ring opening polymerization reaction of the heterocyclic compound during the initial discharge stage of the battery, thereby suppressing the generation of lithium dendrites. Furthermore, the decomposition of the electrolyte on the surface of the lithium-based metal and the resulting side reactions can be reduced, thereby improving the life characteristics of the lithium-sulfur battery.
[0020] In other words, the heterocyclic compound of the present invention may contain one or more double bonds in order to form a polymer protective film on the surface of the lithium-based metal, and must contain one or more heteroatoms (oxygen atoms or sulfur atoms) in order to exert effects such as imparting polarity and increasing affinity with other solvents in the electrolyte.
[0021] The heterocyclic compound may be a 3-15 membered, preferably 3-7 membered, more preferably 5-6 membered heterocyclic compound. The heterocyclic compound may be a heterocyclic compound unsubstituted or substituted with one or more selected from the group consisting of an alkyl group having 1 to 4 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group (-NO2), an amine group (-NH2) and a sulfonyl group (-SO2). The heterocyclic compound may be a polycyclic compound of a heterocyclic compound and one or more selected from a cyclic alkyl group having 3 to 8 carbon atoms and an aryl group having 6 to 10 carbon atoms.
[0022] When the heterocyclic compound is substituted with an alkyl group having 1 to 4 carbon atoms, the radical is stabilized and side reactions between the electrolyte can be suppressed, which is preferable. When the heterocyclic compound is substituted with a halogen group or a nitro group, a functional protective film can be formed on the surface of the lithium-based metal, which is preferable. In this case, the formed functional protective film is stable as a compact protective film, which allows uniform deposition of the lithium-based metal, and has the advantage of suppressing side reactions between polysulfide and the lithium-based metal.
[0023] Specific examples of the heterocyclic compound include 1,3-dioxolane, 4,5-diethyl-1,3-dioxolane, 4,5-dimethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, 4-methyl-1,3-dioxane and 2-methyl-1,3-dioxane, furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran ,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene. Of these, 1,It is preferred to use 3-dioxolane as the first solvent, but this is not a limitation.
[0024] The first solvent containing such a heterocyclic compound may be contained in a volume ratio of 5 to 50 with respect to 100 volume ratio of the total organic solvent (i.e., the first solvent + the second solvent) contained in the electrolyte for lithium secondary batteries of the present invention (the remainder corresponds to the second solvent). If the first solvent is contained in a volume ratio of less than 5 with respect to 100 volume ratio of the total organic solvent of the present invention, the ability to reduce the amount of polysulfide elution may decrease, and the resistance increase of the electrolyte may not be suppressed, or a problem may occur in which a protective film is not completely formed on the surface of the lithium-based metal. In addition, if the first solvent is contained in a content of more than 50 volume ratio with respect to 100 volume ratio of the total organic solvent of the present invention, the surface resistance of the electrolyte and the lithium-based metal may increase, resulting in a problem of a decrease in the capacity and life of the battery.
[0025] B) A second solvent The second solvent includes at least one of an ether-based compound, an ester-based compound, an amide-based compound, and a carbonate-based compound, and serves to dissolve the lithium salt to allow the electrolyte to have lithium ion conductivity, as well as to elute sulfur, which is a positive electrode active material, to facilitate the electrochemical reaction with lithium. In the case of the carbonate-based compound, it may be a linear carbonate-based compound or a cyclic carbonate-based compound.
[0026] Specific examples of the ether-based compound include one or more selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether, but are not limited thereto. Of these, it is preferable to use dimethoxyethane as the second solvent.
[0027] The ester compound may be at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone, but is not limited thereto. The amide compound may be a conventional amide compound used in the art.
[0028] In addition, examples of the linear carbonate compound include one or more compounds selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethylmethyl carbonate (EMC), methylpropyl carbonate (MPC), and ethylpropyl carbonate (EPC), but are not limited thereto.
[0029] In addition, examples of the cyclic carbonate compound include one or more compounds selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof (such as fluoroethylene carbonate (FEC)), but are not limited thereto.
[0030] On the other hand, if the second solvent is contained in an amount less than the appropriate amount, the lithium salt cannot be sufficiently dissolved, which may result in a decrease in lithium ion conductivity, and the active material sulfur may be precipitated in an amount exceeding the solubility concentration. If the second solvent is contained in an excessive amount, the active material sulfur may be excessively dissolved, which may cause a shuttle phenomenon between lithium polysulfide and the lithium negative electrode to worsen, resulting in a shortened lifespan.
[0031] Meanwhile, the organic solvent including the first solvent and the second solvent may be contained in an amount of 60 to 97% by weight, preferably 65 to 95% by weight, more preferably 70 to 95% by weight, based on the total weight of the electrolyte for lithium secondary batteries of the present invention. If the organic solvent is contained in an amount of less than 60% by weight based on the total weight of the electrolyte for lithium secondary batteries, the viscosity of the electrolyte may increase, causing a problem of reduced ion conductivity, or a problem of lithium salt or additives not completely dissolving in the electrolyte. If the organic solvent is contained in an amount of more than 97% by weight, the concentration of lithium salt in the electrolyte may decrease, causing a problem of reduced ion conductivity.
[0032] C) Lithium salt The lithium salt is an electrolyte salt used to increase ionic conductivity, and examples thereof include LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (C2F5SO2)2NLi, (SO2F)2NLi (i.e., LiFSI), (CF3SO2)2NLi (i.e., LiTFSI), (CF3SO2)3CLi, lithium chloroborane, lithium aliphatic carboxylates having 4 or less carbon atoms, lithium tetraphenylborate, and lithium imide can be mentioned as one or more examples.
[0033] The concentration of the lithium salt can be determined in consideration of ion conductivity, and may be, for example, 0.2 to 2 M, preferably 0.5 to 1 M. If the concentration of the lithium salt is below the above range, it is difficult to ensure ion conductivity suitable for battery operation, and if it exceeds the above range, the viscosity of the electrolyte increases, reducing the mobility of lithium ions, or the decomposition reaction of the lithium salt itself increases, reducing the performance of the battery.
[0034] D) Magnesium chloride The magnesium chloride (MgCl2) reacts with the lithium anode to form a LiCl protective layer on the surface of the anode, and also forms a lithophilic Li-Mg alloy to improve the lithium charge / discharge efficiency and inhibit the growth of dendrites, ultimately contributing to increasing the capacity of the battery by improving the lithium usage efficiency.
[0035] It has been confirmed that the use of magnesium chloride as an electrolyte additive can overcome the low reactivity between lithium and magnesium chloride caused by the native oxide layer on the surface of the lithium negative electrode, and a LiCl protective layer and a Li-Mg alloy can be formed on the surface of the lithium negative electrode at the initial stage of charge / discharge when the native oxide layer on the surface of the lithium negative electrode is destroyed.
[0036] The magnesium chloride may be contained in a content of 0.1 to 1 wt %, preferably 0.5 to 1 wt %, based on the total weight of the electrolyte for lithium secondary batteries. If the magnesium chloride is contained in an amount less than 0.1 wt % based on the total weight of the electrolyte, the effect of improving the life of the electrolyte may be negligible. If the magnesium chloride is contained in an amount exceeding 1 wt %, there may be a problem that the deterioration of the battery is accelerated due to a side reaction between the magnesium chloride and the positive electrode active material.
[0037] E) Lithium nitrate The electrolyte for lithium secondary batteries according to the present invention basically contains lithium nitrate (LiNO3), but may further contain one or more selected from the group consisting of lanthanum nitrate (La(NO3)3), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), lithium nitrite (LiNO2), potassium nitrite (KNO2), and cesium nitrite (CsNO2) as necessary.
[0038] The lithium nitrate may be contained in an amount of 0.1 to 7 wt %, preferably 0.5 to 5 wt %, based on the total weight of the electrolyte for lithium secondary batteries. If the lithium nitrate content is less than 0.1 wt % based on the total weight of the electrolyte for lithium secondary batteries, the coulomb efficiency may be significantly reduced, and if it exceeds 7 wt %, the viscosity of the electrolyte may be increased, making it difficult to operate.
[0039] Next, the lithium secondary battery according to the present invention will be described. The lithium secondary battery includes a positive electrode, a lithium negative electrode, a separator interposed between the positive electrode and the negative electrode, and the electrolyte for the lithium secondary battery. As described above, the electrolyte for the lithium secondary battery includes A) a first solvent, B) a second solvent, C) a lithium salt, D) magnesium chloride, and E) lithium nitrate, and the specific contents are the same as those described above. The lithium secondary battery may be any lithium secondary battery commonly used in the industry, among which a lithium-sulfur battery and a lithium-lithium symmetric cell are preferred.
[0040] Hereinafter, the positive electrode, the negative electrode and the separator in the lithium secondary battery according to the present invention will be described in more detail.
[0041] As described above, the positive electrode included in the lithium secondary battery of the present invention includes a positive electrode active material, a binder, a conductive material, etc. The positive electrode active material may be that applied to a general lithium secondary battery, and may include, for example, a lithium nickel cobalt manganese-based compound (lithium NCM-based compound), and may also include elemental sulfur (S8), a sulfur-based compound, or a mixture thereof. Specifically, the sulfur-based compound is Li2S n (n≧1), organic sulfur compounds or carbon-sulfur complexes (C2S x)n(x=2.5-50, n≧2). The positive electrode active material may include a sulfur-carbon composite. Since the sulfur material alone does not have electrical conductivity, it may be used in combination with a conductive material. The carbon material (or carbon source) constituting the sulfur-carbon composite may have a porous structure or a high specific surface area, and may be any material commonly used in the art. For example, the porous carbon material may be at least one selected from the group consisting of graphite; graphene; carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); and activated carbon, but is not limited thereto. The shape of the porous carbon material is not particularly limited as long as it is spherical, rod-like, needle-like, plate-like, tubular, or bulk-like and can be applied to lithium secondary batteries.
[0042] In addition, the carbon material has pores, and the porosity of the pores is 40 to 90%, preferably 60 to 80%, and if the porosity of the pores is less than 40%, lithium ion transmission may not be performed normally and may act as a resistance component, causing problems, and if it exceeds 90%, mechanical strength may decrease. In addition, the size of the pores of the carbon material is 10 nm to 5 μm, preferably 50 nm to 5 μm, and if the size of the pores is less than 10 nm, lithium ion transmission may be impossible, and if it exceeds 5 μm, battery short circuit and safety problems may occur due to contact between electrodes.
[0043] The binder is a component that aids in binding the positive electrode active material to the conductive material and the like and binding to the current collector. For example, one or more selected from the group consisting of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polyvinylpyrrolidone, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butylene rubber, fluororubber, carboxymethylcellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, and mixtures thereof can be used, but the binder is not necessarily limited thereto.
[0044] The binder is usually added in an amount of 1 to 50 parts by weight, preferably 3 to 15 parts by weight, based on 100 parts by weight of the total weight of the positive electrode. If the content of the binder is less than 1 part by weight, the adhesive strength between the positive electrode active material and the current collector becomes insufficient, whereas if the content of the binder exceeds 50 parts by weight, the adhesive strength is improved, but the content of the positive electrode active material is accordingly reduced, which may result in a lower battery capacity.
[0045] The conductive material contained in the positive electrode is not particularly limited as long as it does not induce side reactions in the internal environment of the lithium secondary battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Representative examples include graphite or conductive carbon. For example, graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, and lamp black; carbon-based substances having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. These may be used alone or in combination, but are not necessarily limited thereto.
[0046] The conductive material is usually added in an amount of 0.5 to 50 parts by weight, preferably 1 to 30 parts by weight, based on 100 parts by weight of the total weight of the positive electrode. If the content of the conductive material is too small, less than 0.5 parts by weight, the effect of improving electrical conductivity cannot be expected, and the electrochemical characteristics of the battery may be reduced, and if the content of the conductive material is too large, exceeding 50 parts by weight, the amount of the positive electrode active material becomes relatively small, and the capacity and energy density may be reduced. The method of incorporating the conductive material into the positive electrode is not greatly limited, and a conventional method known in the art, such as coating on the positive electrode active material, can be used. In addition, if necessary, a conductive second coating layer can be added to the positive electrode active material to replace the addition of the conductive material as described above.
[0047] In addition, a filler can be selectively added to the positive electrode of the present invention as a component for suppressing the expansion of the positive electrode. Such a filler is not particularly limited as long as it does not induce chemical changes in the battery and can suppress the expansion of the electrode, and for example, olefin polymers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber; etc. can be used.
[0048] The positive electrode can be manufactured by dispersing and mixing the positive electrode active material, binder, conductive material, etc. in a dispersion medium (solvent) to prepare a slurry, applying the slurry onto a positive electrode current collector, and then drying and rolling the slurry. The dispersion medium can be, but is not limited to, N-methyl-2-pyrrolidone (NMP), dimethyl formamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, water, and mixtures thereof.
[0049] The positive electrode current collector may be, but is not limited to, platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (In doped SnO2), FTO (F doped SnO2), and alloys thereof, and aluminum (Al) or stainless steel surface-treated with carbon (C), nickel (Ni), titanium (Ti) or silver (Ag). The positive electrode current collector may be in the form of a foil, a film, a sheet, a punched one, a porous body, a foam, or the like.
[0050] The negative electrode is a lithium-based metal, and may further include a current collector on one side of the lithium-based metal. The current collector may be a negative electrode current collector. The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has high conductivity, and may be selected from the group consisting of copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy. In addition, calcined carbon, a non-conductive polymer or a conductive polymer surface-treated with a conductive material, etc. may also be used. In general, a copper thin plate is used as the negative electrode current collector.
[0051] In addition, the negative electrode current collector may be in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with or without fine irregularities on the surface. In addition, the negative electrode current collector is applied to have a thickness in the range of 3 to 500 μm. If the thickness of the negative electrode current collector is less than 3 μm, the current collecting effect is reduced, while if the thickness exceeds 500 μm, there is a problem that the processability is reduced when assembling the cell by folding.
[0052] The lithium-based metal may be lithium or a lithium alloy, which includes an element capable of being alloyed with lithium, and may be, specifically, an alloy of lithium with one or more elements selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al.
[0053] The lithium-based metal may be in the form of a sheet or foil, and in some cases, may be in the form of lithium or a lithium alloy deposited or coated on a current collector by a dry process, or may be in the form of metals and alloys on particles deposited or coated by a wet process, etc.
[0054] A conventional separator may be interposed between the positive electrode and the negative electrode. The separator is a physical separator having a function of physically separating the electrodes, and may be any separator that is used as a conventional separator, and is particularly preferred to have low resistance to ion transfer in the electrolyte and excellent electrolyte humidification. The separator separates or insulates the positive electrode and the negative electrode from each other, while allowing lithium ions to be transported between the positive electrode and the negative electrode. Such a separator may be made of a porous, non-insulating, or insulating material. The separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.
[0055] Examples of polyolefin-based porous membranes that can be used as the separation membrane include membranes formed from polyolefin-based polymers such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, and ultra-high molecular weight polyethylene), polypropylene, polybutylene, and polypentene, either alone or in combination. Examples of nonwoven fabrics that can be used as the separator include nonwoven fabrics made of polymers such as polyphenyleneoxide, polyimide, polyamide, polycarbonate, polyethyleneterephthalate, polyethylenenaphthalate, polybutyleneterephthalate, polyphenylenesulfide, polyacetal, polyethersulfone, polyetheretherketone, and polyester, either alone or in combination. Such nonwoven fabrics are in the form of fibers forming a porous web, and include spunbond or meltblown types made of long fibers.
[0056] The thickness of the separator is not particularly limited, but is preferably in the range of 1 to 100 μm, and more preferably in the range of 5 to 50 μm. If the thickness of the separator is less than 1 μm, the mechanical properties cannot be maintained, and if it exceeds 100 μm, the separator acts as a resistance layer, resulting in a decrease in battery performance. The pore size and porosity of the separator are not particularly limited, but the pore size is preferably 0.1 to 50 μm and the porosity is preferably 10 to 95%. If the pore size of the separator is less than 0.1 μm or the porosity is less than 10%, the separator acts as a resistance layer, and if the pore size is more than 50 μm or the porosity is more than 95%, the mechanical properties cannot be maintained.
[0057] The lithium secondary battery of the present invention including the above-mentioned positive electrode, negative electrode, separator, and electrolyte can be manufactured by a process of placing the positive electrode and the negative electrode opposite each other, interposing a separator therebetween, and then injecting the electrolyte for lithium secondary batteries according to the present invention.
[0058] Meanwhile, the lithium secondary battery according to the present invention can be applied to a battery cell used as a power source for a small device, and can be particularly suitably used as a unit battery of a battery module which is a power source for a medium-sized or large device. In view of this, the present invention also provides a battery module including two or more lithium secondary batteries electrically connected (series or parallel). It goes without saying that the number of lithium secondary batteries included in the battery module can be variously adjusted in consideration of the use and capacity of the battery module. Furthermore, the present invention provides a battery pack in which the battery modules are electrically connected according to a conventional technique in the art. The battery module and the battery pack can be used as a power source for one or more medium-sized or large devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle (HEV), and an electric plug-in hybrid electric vehicle (PHEV); an electric truck; an electric commercial vehicle; or a power storage system, but are not necessarily limited thereto.
[0059] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0060] [Example 1] Preparation of electrolyte for lithium secondary battery First, 1% by weight of lithium nitrate (LiNO3) and 0.1% by weight of magnesium chloride (based on the total weight of the electrolyte) were added to an organic solvent made by mixing 1,3-dioxolane (first solvent) and dimethoxyethane (second solvent) in a 1:1 volume ratio (v / v), and dissolved to a concentration of LiTFSI (lithium salt) of 1M to produce an electrolyte for lithium secondary batteries.
[0061] [Examples 2 to 5, Comparative Examples 1 and 2] Preparation of electrolyte for lithium secondary batteries Except for changing the composition as shown in Table 1 below, the same procedure as in Example 1 was carried out to prepare electrolyte solutions for lithium secondary batteries corresponding to Examples 2 to 5 and Comparative Examples 1 and 2, respectively.
[0062] [Table 1]
[0063] [Examples 6 to 8, Comparative Example 3] Preparation of Lithium-Lithium Symmetric Cell Two electrodes were prepared by cutting and rolling lithium to a thickness of 35 μm on a copper current collector, and used as the positive and negative electrodes, respectively, with the lithium facing each other. Then, a porous polyethylene (PE) separator was interposed between the positive and negative electrodes, and the electrolytes prepared in Examples 1, 3, and 5 and Comparative Example 1 were injected and sealed to prepare coin cell type lithium-lithium symmetric cells.
[0064] [Experimental Example 1] Cycle life evaluation of lithium-lithium symmetric cells For the lithium-lithium symmetric cells prepared in Examples 6 to 8 and Comparative Example 3, the current was 1.0 mA / cm at 25° C. 2 The discharge (lower limit -1V) and charge (upper limit +1V) cycles were repeated at a current density of 1000 mA / s, and the potential was measured over time (cycles). The results are shown in Table 2 below and FIG.
[0065] [Table 2]
[0066] Fig. 1 is a graph showing the cycle life performance of lithium-lithium symmetric cells manufactured according to an embodiment and a comparative example of the present invention, and as shown in Fig. 1 and Table 2, it was confirmed that all of the lithium-lithium symmetric cells of Examples 6 to 8 in which magnesium chloride (MgCl2) was contained in the electrolyte had improved life compared to the lithium-lithium symmetric cell of Comparative Example 3 in which magnesium chloride was not contained in the electrolyte. Furthermore, through the cycle life evaluation of Examples 6 to 8, it was confirmed that the life of the lithium-lithium symmetric cells was further improved as the content of magnesium chloride in the electrolyte was increased.
[0067] [Examples 9 to 13 and Comparative Examples 4 and 5] Production of Lithium-Sulfur Batteries First, 87.5 parts by weight of a sulfur-carbon (CNT) composite (S / C 75:25 weight ratio) as a positive electrode active material, 5 parts by weight of Denka Black as a conductive material, and 7.5 parts by weight of styrene butadiene rubber / carboxymethyl cellulose (SBR / CMC 7:3) as a binder were mixed to prepare a positive electrode slurry composition, which was then applied onto a current collector (Al foil), dried at 80° C. for 12 hours, and rolled using a roll press to prepare a positive electrode (the loading amount was 2.9 mg / cm). 2 Then, the prepared positive electrode and a negative electrode in which lithium having a thickness of 35 μm was cross-rolled on a copper current collector were placed facing each other, and a porous polyethylene (PE) separator was interposed between them. Then, the electrolytes prepared in Examples 1 to 5 and Comparative Examples 1 and 2 were injected and sealed to prepare coin cell type lithium-sulfur batteries.
[0068] [Experimental Example 2] Evaluation of cycle life of lithium-sulfur battery The lithium-sulfur batteries prepared in Examples 9 to 13 and Comparative Examples 4 and 5 were subjected to 0.2C charge / 0.3C discharge cycles in a voltage range of 1.8V to 2.5V in CC mode at a temperature of 25° C., and the capacity-potential according to the charge-discharge cycles was measured (after a stabilization process of initial 0.1C / 0.1C 2.5 cycles and 0.2C / 0.2C 3 cycles, the batteries were driven at 0.3C / 0.5C from the 7th cycle). The results are shown in Table 3 and FIG. 2.
[0069] [Table 3]
[0070] FIG. 2 is a graph showing the cycle life performance of the lithium-sulfur batteries manufactured according to an embodiment of the present invention and a comparative example. As shown in FIG. 2 and Table 3, it was confirmed that all of the lithium-sulfur batteries of Examples 9 to 13, in which magnesium chloride (MgCl) was contained in the electrolyte, had improved life compared to the lithium-sulfur battery of Comparative Example 4, in which magnesium chloride was not contained in the electrolyte.
[0071] Furthermore, when magnesium chloride was similarly contained in the electrolyte at a content exceeding 1 wt % (Comparative Example 5), it was confirmed that the life performance was reduced compared to the lithium-sulfur batteries of Examples 9 to 13, in which magnesium chloride was used within the content range of the present invention (0.1 to 1 wt %). This was due to the early deterioration of the battery caused by a side reaction between magnesium chloride and the positive electrode active material (sulfur), and therefore it can be seen that even if magnesium chloride is used as an additive to the electrolyte, the object of the present invention cannot be achieved unless it is used in an appropriate amount.
Claims
1. a first solvent comprising a heterocyclic compound which may or may not contain one or more double bonds and which contains one or more oxygen atoms and / or sulfur atoms; a second solvent comprising at least one of an ether-based compound, an ester-based compound, an amide-based compound, and a carbonate-based compound; Lithium salts; Magnesium chloride; and Lithium nitrate; an electrolyte for a lithium secondary battery, The electrolyte for a lithium secondary battery is characterized in that the magnesium chloride is contained in an amount of 0.1 to 1% by weight based on the total weight of the electrolyte for a lithium secondary battery.
2. 2. The electrolyte for a lithium secondary battery according to claim 1, wherein the magnesium chloride is contained in an amount of 0.5 to 1 wt % based on the total weight of the electrolyte for a lithium secondary battery.
3. The lithium salts are LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 CO 2 , LiC 4 B.O. 8 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, (C 2 F 5 SO 2 ) 2 NLi, (SO 2 F) 2 NLi, (CF 3 SO 2 ) 2 NLi, (CF 3 SO 2 ) 3 3. The electrolyte for a lithium secondary battery according to claim 1, comprising at least one selected from the group consisting of CLi, lithium chloroborane, lithium aliphatic carboxylate having 4 or less carbon atoms, lithium tetraphenylborate, and lithium imide.
4. 4. The electrolyte for a lithium secondary battery according to claim 1, wherein the concentration of the lithium salt is 0.2 to 2.0 M.
5. The heterocyclic compound is a 3- to 15-membered heterocyclic compound substituted or unsubstituted with one or more selected from the group consisting of an alkyl group having 1 to 4 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group, an amine group, and a sulfonyl group, or a polycyclic compound of a heterocyclic compound and one or more selected from the group consisting of a cyclic alkyl group having 3 to 8 carbon atoms and an aryl group having 6 to 10 carbon atoms. The electrolyte solution for lithium secondary batteries according to any one of claims 1 to 4, characterized in that the heterocyclic compound is a 3- to 15-membered heterocyclic compound substituted or unsubstituted with one or more selected from the group consisting of an alkyl group having 1 to 4 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group, an amine group, and a
6. The heterocyclic compound is, for example, 1,3-dioxolane, 4,5-diethyl-1,3-dioxolane, 4,5-dimethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, 4-methyl-1,3-dioxane, 2-methyl-1,3-dioxane, furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 6. The electrolyte solution for lithium secondary batteries according to claim 1, wherein the thiophene is one or more selected from the group consisting of thiophene, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene.
7. 7. The electrolyte solution for a lithium secondary battery according to claim 1, wherein the ether-based compound of the second solvent is one or more selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.
8. 8. The electrolyte for a lithium secondary battery according to claim 1, further comprising at least one selected from the group consisting of lanthanum nitrate, potassium nitrate, cesium nitrate, magnesium nitrate, barium nitrate, lithium nitrite, potassium nitrite, and cesium nitrite.
9. 3. The electrolyte for lithium secondary batteries according to claim 1, comprising 1,3-dioxolane as a first solvent, dimethoxyethane as a second solvent, LiTFSI as a lithium salt, magnesium chloride, and lithium nitrate.
10. A lithium secondary battery comprising: a positive electrode; a lithium negative electrode; a separator interposed between the positive electrode and the negative electrode; and the electrolyte for lithium secondary batteries according to claim 1.
11. The lithium secondary battery according to claim 10, wherein a LiCl protective layer and a Li-Mg alloy are formed on a surface of the lithium negative electrode during an initial period of charging and discharging the lithium secondary battery.
12. 12. The lithium secondary battery according to claim 10 or 11, wherein the lithium secondary battery is a lithium-sulfur battery or a lithium-lithium symmetric cell.
Citation Information
Patent Citations
Magnesium secondary battery anode material and application thereof
CN103367735A
Grignard reagent derivative-added lithium-sulfur electrolyte, and preparation method and application thereof
CN113224387A
Battery, battery pack, electronic apparatus, motor-driven vehicle, and power storage device, and power system
JP2015128028A
Batteries based on organic sulfur species
JP2020501314A
Electrolyte for lithium secondary battery and lithium secondary battery containing the same
JP2022550941A
